46 The Accuracy of Frailty Scoring and Uptake of Comprehensive Geriatric Assessment (CGA) In Patients Living with Frailty Admitted Through the Emergency Department (ED) In Wythenshawe Hospital. (6th February 2020) - Murphy, A; Briggs, S
Abstract: Introduction: Frailty can be defined as a state of physiological decline related to ageing and its identification is crucial for subsequent management. A Cochrane review found that CGA significantly reduces mortality and institutionalisation at 6 months. 1 Published standards for the hospital state that patients with a clinical frailty score (CFS) of ≥7 should be seen by a geriatrician within one hour of presentation to hospital. We investigated if this was met. Methods: Assigning a CFS to all patients ≥65 was introduced to ED triage in November 2018. Patients scored as ≥4 were identified over a 10-day period. We assessed the accuracy of ED based frailty scoring, subsequent hospital wide CGA uptake and investigated if patient's frailty scores influenced this. We also compared CGA uptake across specialities. Results: Over 10 days, 230 patients entering ED were identified as frail. 33% of patients received CGA. On average, it took 18 hours for a patient to get CGA, and 23 hours for a patient with a CFS ≥7 to receive CGA from a geriatrician. The CFS had no influence on them receiving CGA. Surgical specialities were better than some medical specialities in assessing frailty. 38% of the patient's CFS were correct. Conclusions: The hospital is falling short of the standards set out by the department; suggesting that changes need to be made to the process of CGA. There is currently no hospital-wide proforma for CGA; collecting data on the process is laborious and the triggers for CGA are not working as they should. Adding CGA to the hospital EPR would improve this. Highlighting the patients CFS will encourage referral for CGA. Specialities such as cardiology and respiratory can learn from the systems for the recognition and assessment of frailty in place on surgical wards. Reference: 1. Ellis, et al. Cochrane Review 2017.